PENGARUH PERILAKU INDIVIDU TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH DEPARTEMEN AGAMA PROVINSI RIAU - Rahman, Arrafiqur (E-Journal Cano Ekonomos, 2013)
This research aim to to lay open behavioral influence of individual to officerperformance at Regional Office of Department Religion of Provinsi Riau. Type Researchtaken is Expost-Facto, with technique withdrawal of sampel is Simple Random Samplingamounting to 87 people. Data collected to pass enquette by using scale of Likert, techniqueanalyse data the used is Analysis of Regresi Linear Modestly, by using program of SPSS(Statistical Product For Social Sciene). Result of research is individual behavior have aneffect on signifikan to officer performance at Regional Office of Department Religion ofProvinsi Riau. Form equation the found is Y ï½ 27,451ï« 0,196X ï«ï¥ meaning that changeat individual behavior equal to 1% will result change of officer performance equal to19,6%. Value correlation coefficient found equal to 36% meaning there are relation whichare positive between individual behavior and officer performance and pursuant tocoefficient value of determinasi found by the level of behavioral contribution of individualto officer performance at Regional Office of Department Religion of Provinsi Riau is equalto 13%. To increase officer performance at Regional Office of Department Religion ofProvinsi Riau suggested that can give appreciation to officer which is have achievement toand employees which successful always in running duty.